Biocidas eficientes para control de Salmonella spp, Escherichia Coli y aerobios mesófilos en huevos de gallina comerciales de avícola El Jacalito - Cevallos García, Karla Fernanda (2021)
The determination of the efficiency of the concentration of biocidal agents in the control of Salmonella spp, Escherichia coli and mesophilic aerobes in comercial chicken eggs to extend the useful life time was the objective of the present investigation. Microbiological analyzes of mesophilic aerobes, Salmonella spp and Escherichia coli internal and external, were performed on chicken eggs before the application of biocides to determine the initial microbial load. The study factors applied were the type of biocide (CID 20, Vanodine and Quaternary Ammonium) and its concentration, while the block variable was on days 21 and 28, using a 32 factorial arrangement in Completely Random Block Design (CRBD) independently managed and nine treatments plus one witness were applied. The biocides were applied by nebulization to the chicken eggs according to the treatments, after the storage time (21 and 28 days), microbiological analyzes were performed where a significant reduction in the microbial load was observed, the treatments being T2 (Cid 20: 4 ml/l) and T3 (Cid 20: 5 ml/l) effective in the inhibition of mesophilic aerobes, managing to increase the useful life of chicken eggs by seven days.